Virtual Reality Technology and Museum Exhibit - Hirose, Michitaka (International Journal of Virtual Reality, 2006)
More than 15 years have passed since the word "virtual reality" became popular in our society. Now VR technology is at the stage where realistic application should be discussed. For example, it is said that museums are now a good application field of VR technology. In this paper, recent VR technologies which can be utilized for museum exhibits are introduced. The topics include sophisticated image environments such as IPT (immersive projection technology), image-based world generation methodology, and "real world VR" supported by wearable computers